Penambahan Multi Enzim dan Ragi Tape dalam Ransum Berserat Tinggi (Pod–Kakao) untuk Menurunkan Kolesterol Daging Broiler MULTYENZYM AND YEAST SUPPLEMENTATION IN HIGH CRUDE FIBER RATION (CACCAO-POD) DECREASING MEAT CHOLESTROL OF BROILER - ., Suciani; Parimartha, Ketut Warsa; Sumardani, Ni Luh Gde; Bidura, I Gusti Nyoman Gde; Kayana, I Gusti Ngurah; Lindawati, Sri Anggreni (Jurnal Veteriner, 2012)
An experiment has been conducted to investigate the effect of multy enzym (optizyme enzyme) andyeast addited to caccao-pod in the ration to reduce 6 weeks broiler meat cholesterol. This research used acompletely randomized design (CRD) with four treatments: as a control ration (0% caccao-pod); 15%caccao-pod; 15% cacao-pod + 0,20% optizyme enzyme and 15% caccao-pod + 0,20% yeast, with six replicates.There were five broilers 2 weeks similar on the same weight in each replicate. The experimental diets forthe 6 weeks finishing period were formulated to 20% crude protein and Energy Metabolish (2900 ME kcal/kg) in mash formed diet while drinking water was given ad libitum. The experiment was done 4 weeks.The result there was a significant decreas of cholesterol on the diet content 0,20% optizyme enzyme or0,20% yeast, were reduced distribution body fat and meat cholesterol.
Keywords: Body-fat, cocoa-pod, cholesterol, optizyme enzyme, yeast.